Sedimentology of paralic reservoirs : recent advances (Geological Society special publication, 2017)
Paralic reservoirs reflect a range of depositional environments including deltas, shoreline-shelf systems and estuaries. They provide the backbone of production in many mature basins, and contribute significantly to global conventional hydrocarbon production. However, the range of environments, together with relative sea-level and sediment supply changes, result in significant variability in their stratigraphic architecture and sedimentological heterogeneity, which translates into complex patterns of reservoir distribution and production that are challenging to predict, optimise and manage. This volume presents new research and developments in established approaches to the exploration and production of paralic reservoirs.